Role of phospholipase C in cell invasion and metastasis - Lattanzio, R.; Piantelli, M.; Falasca, Marco (2013)
Phospholipases are enzymes that use phospholipids as substrate and are classified in three major classes A, C and D based on the reaction they catalyse. Phosphatidylinositol-specific Phospholipase C enzymes utilize phosphatidylinositol 4,5-bisphosphate as substrate and cleave the bond between the glycerol and the phosphate to produce important second messenger such as inositol trisphosphate and diacylglycerol. The Phospholipase C members are the most well-known phospholipases for their role in lipid signalling and cell proliferation and comprise 13 isoforms classified in 6 distinct sub-families. In particular, signalling activated by Phospholipase C γ, mostly activated by receptor and non-receptor tyrosine kinases, is well characterized in different cell systems. Increasing evidence suggest that Phospholipase C γ plays a key role in cell migration and invasion. Because of its role in cell growth and invasion, aberrant Phospholipase C γ signalling can contribute to carcinogenesis. A major challenge facing investigators who seek to target Phospholipase C γ directly is the fact that it is considered an “undruggable” protein. Indeed, isoform specificity and toxicity represents a big hurdle in the development of Phospholipase C γ small molecule inhibitors. Therefore, a future development in the field could be the identification of interacting partners as therapeutic targets that could be more druggable than Phospholipase C γ.